2020
DOI: 10.1080/00016357.2020.1758772
|View full text |Cite
|
Sign up to set email alerts
|

Delmopinol – adsorption to and absorption through the oral mucosa

Abstract: Objectives: To investigate the surface chemical changes in dynamic interactions of delmopinol on salivary films on oral mucosa in healthy participants after rinsing with an unbuffered water solution of delmopinol, and to examine the oral tissue disposition of delmopinol in rats after local administration. Material and Methods: The contact angle technique was used to monitor the interaction of delmopinol with the salivary film coating the upper labial mucosa of 10 healthy participants through a 4 h period. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The mouthwash solution was not buffered, however, thereby allowing the saliva of the rinsing person to immediately increase the pH of the solution close to neutral pH. This means that delmopinol, with a pKa-value of 7.1, to great extent will be transformed from its cationic to its non-ionic form, which is rapidly adsorbed and retained in the oral mucosa for up to 4 hours and successively released out of this tissue into the systemic circulation [23]. The complex adsorption of delmopinol can be explained by the pKa-value for delmopinol, the great difference in water solubility between its cationic and non-ionised forms, the pH of the system as well as the concentration of delmopinol in the administered solution [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mouthwash solution was not buffered, however, thereby allowing the saliva of the rinsing person to immediately increase the pH of the solution close to neutral pH. This means that delmopinol, with a pKa-value of 7.1, to great extent will be transformed from its cationic to its non-ionic form, which is rapidly adsorbed and retained in the oral mucosa for up to 4 hours and successively released out of this tissue into the systemic circulation [23]. The complex adsorption of delmopinol can be explained by the pKa-value for delmopinol, the great difference in water solubility between its cationic and non-ionised forms, the pH of the system as well as the concentration of delmopinol in the administered solution [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, the influence of delmopinol on the oral mucosa was studied, and it was shown that delmopinol was rapidly adsorbed and retained in this tissue [23]. It was suggested that the interaction between delmopinol and mucosal surfaces should be of great importance for the pharmacokinetics of delmopinol as well as for some adverse effects (a transient numbing…”
Section: Introductionmentioning
confidence: 99%
“…In dentistry, EOs could be appropriate as preoperative rinses, in periodontal procedures, in post-treatment applications or as a conventional mouthwash [79] About DEL, it was formulated as an agent with reduced antimicrobial activity and to prevent the disruption of healthy oral microbial flora [84]. This compound inhibits the formation of new plaque by counteracting the enzymes involved in the stability of the plaque matrix [85]. Although tooth staining is reported as an adverse effect of DEL, it is greatly minor when compared to CHX [102].…”
Section: Major Oral Antiseptics In Current Clinical Practicementioning
confidence: 99%